Accountability of central banks: aspects and quantification - DE HAAN, J.; AMTENBRINK, F.; EIJFFINGER, S.C.W. (PSL Quarterly Review, 2013)
The work examines the relationship between central bank independence and accountability. The authors do this by using an indicator for central bank accountability based on the laws of 16 central banks. Central bank accountability is identified as having three distinct features, namely, the explicit definition and ranking of the objectives of monetary policy, the transparency of the actual monetary policy, and the final responsibility to monetary policy. JEL Codes: E58